Coal mine management in East Kalimantan: a review of public policy - Devi Triady; Dewi Saraswati (Monas: Jurnal Inovasi Aparatur, 2021)
The problems posed by coal mining in East Kalimantan have an environmental impact and an imbalance of economic growth with social development. In practice, mine management that does not meet the principles of good management, such as corrupt practices, uncontrolled mining permits, indicates the need for a particular study related to coal mining policies and regulations in East Kalimantan Province. Therefore, this paper is intended to analyze aspects of coal mining policy and regulation as well as policy implications to improve coal mining governance, especially in the perspective of preventing corruption in coal mining management in East Kalimantan. This research uses the desk study method with descriptive analysis of related literature related to coal mining management, especially in East Kalimantan. The results of this study indicate that the governance of coal mining in East Kalimantan needs to be improved in the context of Law Number 3 of 2020 concerning Amendments to Law Number 4 of 2009 concerning Mineral and Coal Mining through the application of natural resource management principles as well as the application of the concept of governance. , the need to improve policies and governance of coal mines (licensing, transparency, and law enforcement) and the need to strengthen the institutional system in the management of this mine.